ANALISIS KOMPORATIF ALIRAN TEOLOGI ISLAM KLASIK: STUDI KRITIS PEMIKIRAN KHAWARIJ, MURJI’AH, DAN MU’TAZILLAH TERHADAP KONSTRUKSI AKIDAH KONTEMPORER - Bayu Bambang Nurfauji; Lisa Rahma Agustina; Mia Ramdayani Zahro; Alimudin; Nena Aliza (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
Theological issues in Islam constitute a fundamental discourse that emerged in the early period following the passing of the Prophet Muhammad (peace be upon him), triggered by political tensions that later transformed into theological debates. This article aims to provide an in-depth analysis of three major theological schools in classical Islamic history, namely the Khawarij, Murji’ah, and Mu‘tazilah, as well as the implications of their thought for the concepts of faith (īmān), disbelief (kufr), and human actions. The main focus of this study is to explore the historical background of the emergence of each school,  their central doctrines, and the methods of reasoning they employed in interpreting religious texts. The research method used is qualitative, employing a library research approach. This analysis concludes that although these three schools have distant historical roots, their patterns of thought continue to appear in fragmented forms within the dynamics of modern Islamic thought. Therefore, a comprehensive understanding of classical theological history is crucial to preventing religious extremism